Launching the Phnom Penh Stock Exchange: Toward a Legal Framework for Launching a Stock Exchange in an Underdeveloped Country - Gottlieb, Jason (Columbia Journal of Asian Law, 2000)
The idea of launching a capitalist stock exchange in an underdeveloped country where capital was abolished just thirty years ago seems optimistically free-market, if not naively silly. However, examining the possibility of launching the Phnom Penh Stock Exchange can serve as a cipher for examining the problem of economic development in the so-called “third world” in general. Furthermore, such an analysis can be useful to thinking about how a generalized legal and regulatory framework can be customized to help a country address its economic development in the context of its own markets, culture, and brand of democracy. Launching any stock exchange is a massive structural effort, and Cambodia is a prime example of the extra difficulties that a developing country faces in such an undertaking. The list of problems faced by developing countries is a long one: lack of initial capital, lack of investment opportunities, lack of reliable information, lack of infrastructure, corruption, and the difficulties (especially in former communist states) of learning capitalism from the ground up. But despite this formidable list, the experience of quite a few developing countries in the last thirty years has shown that launching a stock exchange is not only possible, but can be a boon to economic development.